Hospital‐based influenza surveillance in Korea: Hospital‐based influenza morbidity and mortality study group12. Issue 5 (18th March 2013) - Song, Joon Young; Cheong, Hee Jin; Choi, Sung Hyuk; Baek, Ji Hyeon; Han, Seung Baik; Wie, Seong‐Heon; So, Byung Hak; Kim, Hyo Youl; Kim, Young Keun; Choi, Won Suk; Moon, Sung Woo; Lee, Jacob; et al.
Abstract Influenza epidemics occur annually with variations in size and severity. Hospital‐based Influenza Morbidity & Mortality was established to monitor influenza epidemics and their severity, which is composed of two surveillance systems: emergency room‐based and inpatient‐based surveillance. Regarding emergency room‐based surveillance, influenza‐like illness index (influenza‐like illness cases per 1, 000 emergency room‐visiting subjects), number of laboratory‐confirmed cases and the distribution of influenza types were estimated weekly. Inpatient‐based surveillance included monitoring for hospitalization, complications, and mortality. The emergency room influenza‐like illness index correlated well with the number of laboratory‐confirmed influenza cases, and showed a bimodal peak at Week 4 (179.2/1, 000 emergency room visits) and Weeks 13‐14 (169.6/1, 000 emergency room visits) of 2012. Influenza A was the predominant strain during the first epidemic peak, while influenza B was isolated exclusively during the second peak. In 2011–2012 season, the mean admission rate of emergency room‐visiting patients with influenza‐like illness was 16.3% without any increase over the epidemic period. Among the hospitalized patients with influenza, 33.6% (41 out of 122 patients) were accompanied by complications, and pneumonia (28.7%, 35 out of 122 patients) was the most common. Most fatal cases were caused by influenza A (96.2%) after the first epidemic peak. In conclusion, Hospital‐based Influenza Morbidity & Mortality was effective for monitoring the trends in circulating influenza activity concurrently with its severity. In the 2011–2012 season, the influenza epidemic persisted for a ≥5‐month period, with a bimodal peak of influenza A and B in sequence. Overall, influenza A was more severe than influenza B. J. Med. Virol. 85:910–917, 2013. © 2013 Wiley Periodicals, Inc.